Needle stick injuries prevalence among nurses in Jordanian hospitals - Juni, Muhamad Hanafiah; Abdul Rahman, Anita; Md Said, Salmiah; A., Hamdan Mansour (Community Health Society Malaysia, 2015)
Background: Needle Stick Injuries (NSI) is one of the most significant hazard threatening the well-being of nurses and other healthcare workers inside hospitals. The current situation of NSI, practices and its associated factors, among nurses has not been thoroughly examined in Jordanian hospitals. Objectives: The objectives of this study are to determine the prevalence of NSI among Jordanian nurses, and to identify the risk factors associated with these injuries. Methods: A cross-sectional study was conducted in February 2015 as a pilot study among108 nurses in Jordan University Hospital, and The Specialty Hospital. The subjects were selected using stratified random sampling. The data were collected using a self-administered questionnaire. The data were analyzed using International Business Machines Corporation Statistical Product and Service Solutions (IBM SPSS) version21. Results: The results showed that within the last 3 months, 67.6% (95% CI: 1.88%, 2.19%) of the nurses reported having at least one NSI. Most of these injuries were caused by recapping procedure, while working with syringe needles, and occurred during morning shifts. The prevalence of NSI was found to be significantly associated with age group (P<0.001), working experience (P<0.001), and marital status (P<0.004). Conclusion: The reported prevalence of NSI among Jordanian nurses is alarming, thus further investigations are needed to understand the underlying factors behind this high prevalence rate, and also to investigate the knowledge of the nurses about NSI and their practices while working with needles.